KURIKULUM MERDEKA DALAM KERANGKA AKSES PENDIDIKAN: TINJAUAN LITERATUR ATAS INISIATIF UNICEF DAN PEMERINTAH INDONESIA - Muhammad Sukron Fauzi; Mumu Muzayyin Maq; Ai Rukmini; Muhammad Arsyad; Arditya Prayogi; Edi Ahyani (LPPM Universitas Ekasakti, 2024)
This study aims to explore how the Kurikulum Merdeka is implemented within the framework of a more inclusive education access, considering the support from UNICEF and the policies of the Indonesian government. This research is a literature review, designed to collect, analyze, and synthesize various relevant sources of information to provide a comprehensive overview of the subject. Literature review research focuses on gathering, analyzing, and synthesizing information from diverse sources related to a specific topic or issue. The findings of this study indicate that UNICEF focuses on protecting children's rights and improving access to quality education through curriculum development, teacher training, and infrastructure enhancement. The Kurikulum Merdeka in Indonesia, with its flexible and competency-based approach, aligns with international education models that emphasize relevance and holistic assessment. Despite challenges such as infrastructure limitations and a shortage of qualified educators, the Kurikulum Merdeka reflects similar efforts to those of UNICEF and global practices in enhancing education quality and access.